海底甲烷水合物溶解和分解辨析及其地质意义 - 雷怀彦; 官宝聪; 龚承林; 刘建辉; 黄磊 (2007)
甲烷水合物的溶解和分解过程是甲烷水合物成藏的关键科学问题,同时也是造成环境灾害事件的重要因素。近年来,在阅读甲烷水合物相关文献中发现有些作者对甲烷水合物溶解和分解的复杂动力学过程产生了一些混淆,并由此可能对甲烷水合物的成藏机理及其对环境气候变化影响的认识造成偏差。基于前人的大量研究成果,并结合作者多年对甲烷水合物形成和分解动力学过程的系统研究,认为海底存在一种甲烷气体的动态存储与排泄平衡作用,甲烷水合物的溶解和分解是海底甲烷气的主要排泄方式,也是甲烷水合物失稳后的2种不同的重要过程,同时,海底甲烷气的排泄量、运移方式和排放速率都与甲烷水合物成藏与否密切相关,因此深入认识甲烷水合物溶解和分解过程的控制机理,对海底甲烷水合物形成机制、成藏过程的研究和对全球碳循环、气候变化的评估有着重要的科学意义。 The dissolution and dissociation of methane hydrate in seawater are key scientific problems in the formation mechanisms of methane hydrate.They are also the important factors causing environmental disasters and geologic hazards.In recent years,there was some confusion in literatures about the kinetics of dissolution and dissociation processes,and there were some warped understanding of their influence on methane hydrate formation and global climate change.Based on a lot of research results,we think that marine methane has a homeostasis between storage and drainage.And dissolution and dissociation are the major dejection manners of methane hydrate.It is critical to realize that the both are two different processes.In addition,output,migration manner and drainage rate about marine methane are all related to the formation of methane hydrate.Therefore,it is important to discriminate the kinetic processes of methane hydrate dissolution and dissociation in seawater. 国家自然科学基金项目(编号:40472156);; 教育部厦门大学“211”工程项目;; “985”二期工程资助项目联合资助